Mandatory Refererence to the OECD Commentary for Tax Treaty Interpretation PURPOSES - is it necessary? A Case Study of the New Protocol to 2002 Indonesia – the Netherlands Tax Treaty signed on 30 July 2015 - Sukardi, Ichwan (Technology and Economics Law Journal, 2023)
The Indonesia-Netherlands Double Taxation Agreement (“DTA”) has been renegotiated and amended several times until the latest amendment which was made in 2015 whereby a new protocol was produced. What is interesting about this new protocol is the requirement to refer to the OECD Commentary in interpreting the DTA articles that are identical and similar to OECD Model, especially in relation to the term “Beneficial Owner”. Over the last two decades, the usage of Dutch SPVs in financing structure have triggered many tax disputes between the Tax Authority in Indonesia (the Directorate General of Taxation or “DGT’) and the Indonesian taxpayer. The DGT would typically reject the treaty benefit for using WHT exemption for interest payment and impose the 20% WHT rate instead. However, it is in the core interests of the Dutch to maintain its position of being the hub for investors to enter into the European financial market, and therefore it is of much importance for it to secure favorable treaty provisions ,despite the fact that the WHT rate on interest payment has since been amended to 5%. On the other hand, we are all aware that the Commentary is designed as a reference in interpreting the treaty, and shall not be the legal binding instrument, as expressed by the Committee on Fiscal Affairs. On this basis, most of the scholars view that there is no legal binding status of the Commentary to parties signing the DTA. The VCLT (Vienna Convention on the Law of Treaties), though, requires good faith in the interpretation of the treaties, and Indonesia’s position on how to interpret the treaty should pave the way for us to recognize that there is no such rejection on referring to the Commentary in interpreting the DTAs.